Cerebrospinal fluid BDNF pro-peptide levels in major depressive disorder and schizophrenia. (June 2019) - Mizui, Toshiyuki; Hattori, Kotaro; Ishiwata, Sayuri; Hidese, Shinsuke; Yoshida, Sumiko; Kunugi, Hiroshi; Kojima, Masami
Abstract: The role of brain-derived neurotrophic factor (BDNF) and its related molecules has been extensively studied in the context of psychiatric disorders. In the present study, we focused on the newly identified BDNF pro-peptide, which is generated together with mature BDNF by proteolytic processing of their precursor, proBDNF. Here, we report, for the first time, that BDNF pro-peptide is present in human cerebrospinal fluid (CSF) and quantifiable by western blotting. We measured CSF BDNF pro-peptide levels in 27 patients with schizophrenia, 18 patients with major depressive disorder (MDD), and 27 healthy controls matched for age, sex, and ethnicity (Japanese). The ratio of the BDNF pro-peptide level to the total protein level in MDD patients was significantly lower than that in controls (Kruskal-Wallis with Dunn's multiple comparisons test; p = 0.046). When men and women were examined separately, males with MDD had a significantly lower BDNF pro-peptide/protein ratio than male controls (p = 0.047); this difference was not found in female subjects. The ratio tended to be lower in male schizophrenia patients (p = 0.10). Although we tried to measure the levels of mature BDNF in CSF, they were below the limit of detection of the ELISA and multiple analyte profiling technology. Taken together, the results suggest that reduced CSF BDNF pro-peptide levels are associated with MDD, particularly in males. Further studies involving a larger sample size are warranted.